Schaum's outline of data structures with Java - Hubbard, J. R. 1943- 4 0 (John Rast),16; 5 (New York : McGraw-Hill, 2007)
Provides an overview of data structures with JAVA and includes 260 example problems with step-by-step solutions, explanations of ideal programming language for the Internet; and more.
Includes index.;Cover title: Data structures with Java.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Data structures (Computer science);Java (Computer program language);Computer programming;Java (Computer program language);Computer programming;Data processing. -- Problems, exercises, etc.;Problems, exercises, etc; 20; 2